An international collaborative study to compare different von Willebrand factor glycoprotein Ib binding activity assays: the COMPASS‐VWF study. (19th July 2018) - Szederjesi, A.; Baronciani, L.; Budde, U.; Castaman, G.; Lawrie, A. S.; Liu, Y.; Montgomery, R.; Peyvandi, F.; Schneppenheim, R.; Várkonyi, A.; Patzke, J.; Bodó, I.
Abstract : Essentials New VWF activity assays are increasingly used but information on their comparability is limited. This is an ISTH SSC‐organized study (expert labs, 5 countries) to compare all available assays. VWF activity by six assays correlated well with each other. The new assays show improved characteristics ‐ minor differences are noted. Summary: Background: Several new assays have become available to measure von Willebrand factor (VWF) activity. The new assays appear to have improved performance characteristics compared with the old reference standard, ristocetin cofactor activity (VWF:RCo), but information is limited about how they compare with VWF:RCo and each other. Methods: The von Willebrand factor Subcommittee of the International Society for Thrombosis and Haemostasis (ISTH) Scientific and Standardization Committee (SSC) designed a collaborative study involving expert laboratories from several countries to compare available tests with each other and with VWF:RCo. Eight laboratories from five countries were provided with blinded samples from normal healthy individuals and well‐characterized clinical cases. Laboratories measured VWF activity using all tests available to them; data from six laboratories, not affected by thawing during transportation, are included in this study. Results: All tests correlated well with VWF:RCo activity ( r ‐values ranged from 0.963 to 0.989). Slightly steeper regression lines for VWF:Ab and VWF:GPIbM were clinically insignificant. The new assays showed improved performance characteristics. Of the commercially available assays, the VWF:GPIbR using the AcuStar system was the most sensitive and could reliably detect VWF activity below 1 IU dL −1 . The lower limit of the measuring interval for the VWF:GPIbM and the VWF:GPIbR assays was in the 3–4 and 3–6 IU dL −1 range, respectively. Inter‐laboratory variation was also improved for most new assays. Conclusion: All VWF activity assays correlated well with each other and the VWF:RCo assay. The slight differences in characteristics found in the COMPASS‐VWF study will assist the VWF community in interpreting and comparing activity results.